Contribution to the knowledge of Siphonoperla in Europe (Plecoptera: Chloroperlidae): Siphonoperla korab sp. n. - Graf, Wolfram; Popijač, Aleksandar; Previšić, Ana; Gamboa, Maribet; Kučinić, Mladen (Zootaxa, 2012)
A new species of stonefly of the genus Siphonoperla from the Dinaric Mountains of Macedonia is described. The descrip-tion of S. korab sp. n. is based on morphological and genetic characters. We also provide notes on habitat and distribution of this new taxon. Further notes on the biogeography of the genus are added.